Why should I? : a book about respect - Graves, Sue.; Carletti, Emanuela Guicciardini, Desideria (Great Britain: The Watts Publishing Group, 2020)
Arin struggles with showing respect for other people. But when everyone gets upset with him, Arin feels upset, too. Can he learn that treating others with respect will make them, and him, happier?
Keywords: Emotions and behavior. -- Respect. -- Juvenile Literature